TTIP: Political and economic rationale and implications - Jacques Pelkmans; Thea M. Lee; Federica Mustilli; Lucian Cernat; Ana Norman-López; Alessandra Tucci; Monique Goyens; Léa Auffret; Galina V. Kolev; Jürgen Matthes (Intereconomics, 2015)
The Transatlantic Trade and Investment Partnership will reduce tariffs and lower regulatory hurdles that currently impair trade between the EU and the US. However, TTIP has been controversial from the outset. Non-governmental organisations are concerned about lowered health and environmental standards, unions fear a further weakening of labour conditions, and economists debate whether or not there will actually be any noticeable impact on employment and GDP growth. This Forum, featuring contributions by the speakers at the 2015 Intereconomics conference, presents a balanced overview of both the prospective benefits as well as the possible drawbacks to the potentially monumental trade agreement.
Keywords: 330; Freihandelszone; EU-Staaten; USA; TTIP-Staaten